Raman Spectroscopy and Electrochemical Investigations of Pt Electrocatalyst Supported on Carbon Prepared through Plasma Pyrolysis of Natural Gas - Tereza Cristina Santos Evangelista; Giordano Toscano Paganoto; Marco Cesar Cunegundes Guimarães; Josimar Ribeiro (Journal of Spectroscopy)
Physicochemical and electrochemical characterisations of Pt-based electrocatalysts supported on carbon (Vulcan carbon, C1, and carbon produced by plasma pyrolysis of natural gas, C2) toward ethanol electrooxidation were investigated. The Pt20/C180 and Pt20/C280 electrocatalysts were prepared by thermal decomposition of polymeric precursors at 350°C. The electrochemical and physicochemical characterisations of the electrocatalysts were performed by means of X-ray diffraction (XRD), transmission electron microscope (TEM), Raman scattering, cyclic voltammetry, and chronoamperometry tests. The XRD results show that the Pt-based electrocatalysts present platinum metallic which is face-centered cubic structure. The results indicate that the Pt20/C180 electrocatalyst has a smaller particle size (10.1–6.9 nm) compared with the Pt20/C280 electrocatalyst; however, the Pt20/C280 particle sizes are similar (12.8–10.4 nm) and almost independent of the reflection planes, which suggests that the Pt crystallites grow with a radial shape. Raman results reveal that both Vulcan carbon and plasma carbon are graphite-like materials consisting mostly of sp2 carbon. Cyclic voltammetry and chronoamperometry data obtained in this study indicate that the deposition of Pt on plasma carbon increases its electrocatalytic activity toward ethanol oxidation reaction.